Challenges in the search for gravitational wave signals - Ferreira, Tábata Aira (Cadernos de Astronomia, 2026)
This paper presents the challenges faced in the search for gravitational-wave signals by the LIGO detectors, arising from the presence of noise in the data. Such noise can couple to the interferometers through different physical mechanisms associated with the environment or the instrumentation. As a consequence, it can affect the parameter estimation of real detections, reduce the statistical significance of observed events, or, in some cases, mimic astrophysical signals.
Keywords: gravitational waves; LIGO; noise